The Effect of Profen and Vitamin C on rate of Sperm abnormalties and Weight of Testes and Prostate Gland of Male White Mice - Raheem, Aseel (University of Thi-Qar Journal of Science, 2012)
The present research was conducted on 36 white mice of similar weights by using one of the non-steroid anti-inflammation drugs, namely profen. Vitamin C was used to assess the sperm abnormality; the testes mean weight, and prostate gland weight. The mice were divided into three equal groups. The mice of the first group were injected with profen (200mg. /kg. for each), the second was injected with profen and vitamin C (200mg. /kg. for each), and the third group was the control one. The mice of the first two groups were injected, in the peritoneum membrane once a day for a month. The treatment with profen resulted into an increase in the percentage of the abnormal sperms compared to the control group (10.74 ± 1.92 and 4.17 ± 1.26 respectively). The results have shown that the treatment with vitamin C and profen led to a decrease in the percentage of the abnormal sperms compared to the profen group (10.74 ± 1.92). The statistical analysis has shown considerable differences (P< 0.05) for this group compared to the control one; this means that the use of vitamin C with profen decreases the percentage of abnormality effected by profen. Also, there happened a considerable decrease (P< 0.05) inthe testes weight treated with profen (2526.8 ± 6.48 mg.) compared to the control group (3203 ± 9.9 mg.). However, the testes weight was high in the group treated with profen and vitamin C (3245.5 ± 13.8 mg.)